Definition of an increasing function - Robertas Vilkas (Lietuvos Matematikos Rinkinys)
Some nuances of applications of the general definition of an increasing (decreasing, non-decreasing, non-increasing) function are discussed. The question of concern to teachers is answered:  can a function be increasing not only on an open interval?